Knowledge of obstetric danger signs and associated factors among pregnant women attending the antenatal care clinic at Kenyatta National Hospital: A cross-sectional study. (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Pregnancy is a normal phenomenon accompanied by physiological, psychological, andemotional changes. However, some changes negatively affect the health of mothers and babies,increasing maternal and neonatal mortality and morbidity. Obstetric danger signs show immediatehazards that, if not avoided, may lead to severe injuries or death to the pregnant mother or unborn child.However, data on the awareness of obstetric danger signs in Kenya are scarce. This study aimed toassess the knowledge of obstetric danger signs and associated factors among pregnant women in aselect Kenyan population.Methods: A descriptive cross-sectional study was conducted at the Kenyatta National Hospital antenatalcare clinic. Researcher-administered questionnaires were used in data collection. Quantitative data wereanalyzed using descriptive analysis; inferential statistics were used to determine the association betweenvariables. A p-value of